Gamification in Healthcare: Bibliometric Analysis on Gamification in Nursing Care - Çankaya, Askeri (wiley, 2025)
Gamification in healthcare is an approach that increases patient engagement and is considered a fun technique. Basically, it can be defined as the application of game rules in a nongame area. In this study, studies in the Web of Science (WoS) database on gamification in nursing care in health services were examined. In the advanced and detailed search, ("digital game'' OR ''gamif*'' OR ''serious games'' OR ''game-based learning'') AND ("health* OR ''medical'' OR ''rehabilitation'' OR ''nursing") AND ("healthcare'' OR ''nursing care") keywords were used in the WoS database. WoS bibliographic database was used in RStudio software to analyze the articles. Fifty-one articles published between 2011 and 2024 were analyzed bibliometrically. Fourteen articles were published between 2011 and 2019, and 37 articles were published between 2020 and 2024. The mean citation count per article is 12.08. There are 287 authors in 51 published articles. There is an average of 8.88 co-authors per article. A total of 219 keywords were used in the articles. Researchers preferred to use the keywords "gamification", "education", "nursing", and "serious game" in their studies. A total of 15.6% of the articles were published in "Frontiers in Pediatrics", "Games for Health Journal", "Healthcare", and '' Journal of Clinical Nursing" journals. It was determined that the first study on gamification in nursing care was conducted in 2011 and the studies have increased since 2020. The swift advancement of technology, along with its application developments in healthcare and nursing care, and the integration of patients into care offer a chance to enhance their participation in disease management and encourage healthy habits that improve their health status. This study aims to guide researchers by highlighting key points for future research on gamification in nursing care. © 2025 Scrivener Publishing LLC. All rights reserved.
Keywords: Bibliometric analysis; Gamification; Healthcare; Nursing care; Web of science